First plasma exposure of a pre-damaged ITER-like plasma-facing unit in the WEST tokamak: procedure for the PFU preparation and lessons learned. (1st May 2022) - Richou, Marianne; Corre, Yann; Loewenhoff, Thorsten; Diez, Mathilde; Martin, Céline; Aretz, Anke; Coenen, Jann Willem; Firdaouss, Mehdi; Giacometti, Gregory; Grosjean, Alex; Pintsuk, Gerald; Roche, Hélène; et al.
Abstract: The evaluation of the impact of plasma-facing components damage on subsequent plasma operation is an important issue for ITER. During the first phase of the operation of WEST, a few ITER-like divertor plasma-facing units (PFUs) have been installed on the lower divertor. One PFU was pre-damaged under electron beam gun thermal loading, before its installation in WEST, and the subsequent evolution of the damage was studied after the WEST plasma exposure. This paper presents the procedure followed to get the pre-damaged PFU. It consists of the characterization of the response of tungsten samples representative of WEST PFU under high heat flux (HHF) loading, the selection of damage (namely, small cracks, crack network, crack network, and W melt droplets). Finally, according to the WEST plasma loading conditions, the blocks with damage within the PFU and the position of the pre-damaged PFU on the WEST lower divertor are attributed. The first results obtained after an initial plasma exposure in WEST lead to the assessment, as expected with regard to the heat loading conditions, that no major surface aspect modification was found. This result emphasized the possibility of implementing as pre-damaged small droplets of melted tungsten in a high heat-loaded zone for a future WEST experimental campaign.